Animal power: Outdated or underestimated? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
People have used animals as beasts of burden and of cultivation since the early days of agriculture. Buffalo, cattle, horses, donkeys, mules, camels, elephants and even dogs have played crucial roles in food production and transportation in a...